Treatment of type 2 diabetes mellitus using the traditional Chinese medicine Jinlida as an add-on medication: A systematic review and meta-analysis of randomized controlled trials - Zhao, Xuemin; Liu, Linfei; Liu, Jing (Frontiers in Endocrinology, 2022)
Background Numerous randomized controlled trials (RCTs) conducted in China have shown that jinlida granules are a promising traditional Chinese medicine (TCM) for the treatment of persons with type 2 diabetes mellitus (T2DM). Controversial results have been reported in different RCTs. The aim of our study was to evaluate the adjuvant hypoglycemic effect of jinlida granules on persons with T2DM and to explore the source of heterogeneity between these RCTs. Materials and methods Medical article databases were individually searched by two authors for RCTs that provided data regarding the effect of jinlida granules in the treatment of T2DM before 1 June 2022. The methodological quality of the included RCTs was comprehensively assessed by two authors. Data from RCTs with low risk of bias were pooled using Stata SE 12.0 (random-effects model). Evidence derived from the meta-analysis will be assessed according to the GRADE system. Results Twenty-two RCTs were eventually included in the systematic review and three RCTs with low risk of bias were analyzed in the meta-analysis. Compared with the control groups, significant changes were found in lowering glycosylated hemoglobin a1c (mean difference -0.283 with 95% CI -0.561, -0.004; P=0.046), and were not found in lowering 2-hour postprandial glucose (mean difference -0.314 with 95% CI -1.599, 0.972; P=0.632) and fasting blood glucose (mean difference -0.152 with 95% CI -0.778, -0.474; P=0.634) in the jinlida groups. The GRADE-assessed evidence quality for the outcomes was moderate. Conclusion The adjuvant hypoglycemic effect of jinlida granules on adult Chinese persons with T2DM was statistically found in lowering HbA1c and was not statistically found in lowering FPG and 2h-PG. Evidence grading should be considered moderate, and the results should be interpreted cautiously. Whether the efficacy of HbA1c-lowering related to clinical significance remains to be investigated in future RCTs. Differences in HbA1c, FPG and 2h-PG at baseline and high risk of bias were important source of heterogeneity between these RCTs. In order to objectively evaluate the efficacy of jinlida granules on T2DM, it is urgently needed that high-quality RCTs evaluating the hypoglycemic effect of jinlida granules in the treatment of qi-yin deficiency pattern T2DM. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42018085135.